1980
DOI: 10.1172/jci109904
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygen in antibody-dependent cytotoxicity mediated by monocytes and neutrophils.

Abstract: A B S T R A C T The antibody-dependent cell-mediated cytoxicity (ADCC) by human monocytes and neutrophils was investigated by measuiriing the release of 'chromate from prelabeled erythrocytes coated with immunoglobulin G. ADCC was found to be positively correlated to phagocytosis of 51Cr-labeled erythrocytes and to the postphagocytic events of the effector cells, activation of the hexose monophosphate shunt, and degranulation.Exclusion of oxygen from the incubatioin media halved the ADCC by both cell types wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…Indeed, MPO-deficient granulocytes successfully destroyed both erythrocyte3 and endothelial cell targets (23). Recent reports have also demonstrated that human monocytes and neutrophils can destroy target cells in antibody dependent (14,(50)(51)(52) or serum independent systems (53 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MPO-deficient granulocytes successfully destroyed both erythrocyte3 and endothelial cell targets (23). Recent reports have also demonstrated that human monocytes and neutrophils can destroy target cells in antibody dependent (14,(50)(51)(52) or serum independent systems (53 …”
Section: Discussionmentioning
confidence: 99%
“…24 Regarding a role of Bcl-2 proteins in this process, one should realize that PMNs are considered to possess no or only few rudimentary mitochondria, which do not play a role in the active life of the cell. 29,30 Therefore, PMNs have been considered to be "a nonmitochondrial scene" of apoptosis. 23 On the other hand, mitochondria constitute a crossroad of apoptosis regulation between members of the Bcl-2 family and the caspases.…”
Section: Introductionmentioning
confidence: 99%
“…Their contribution to ADCC, however, has not been unequivocally demonstrated. A participation of reactive oxygen species had been described in lysis of antibody-coated erythrocytes, 14,15 but not for tumor cells lysis. [16][17][18] Moreover, inhibition of RNA or protein synthesis apparently did not inhibit the ADCC, 10 implying preformed mediators.…”
Section: Introductionmentioning
confidence: 99%